POTENTIAL LEAVES OF TREMBESI (Albizia saman (Jacq.) Merr.) AS BIOACCUMULATORS FOR HEAVY METAL (PB) IN MANADO CITY - Albertin Indriani; Bobby J. V. Polii; Tommy Ogie (Sam Ratulangi University, 2021)
This research is a survey study that aims to determine the lead (Pb) content in the leaves of trembesi (Albizia saman (Jacq.) Merr.) in Taman Kesatuan Bangsa, Jalan Boulevard, and Tugu Boboca, and to see the relationship between traffic density and lead (Pb) content. on the leaves of trembesi (Albizia saman (Jacq.) Merr.) in the National Unity Park, Jalan Boulevard, and Tugu Boboca. The results showed that the heavy metal content of lead (Pb) in Manado City, in several places such as Taman Kesatuan Bangsa, Jalan Boulevard, and around Tugu Bobocca ranged from 0.59 to 0.84 Ppm. Based on the quality standard of Pb in the air according to PP No. 41 of 1999 of 2 g/Nm3 Pb content in the city of Manado is still below the threshold for Pb quality standards in the air. However, when compared with environmental quality standards for Pb parameters in the air according to WHO, the maximum permissible limit is 0.5 g/Nm3. Pb content has exceeded the threshold for Pb contamination in the air according to WHO standards. The relationship between traffic density and lead (Pb) content in trembesi leaves shows that there is a relationship between the number of motorized vehicles and the Pb content in trembesi leaves, but the relationship between the number of motorized vehicles and the Pb content is moderate. The high and low Pb content in the leaves is not only influenced by the large number of vehicles that pass on the road, but there are other factors, namely wind direction and speed, and the distance of the tree from the pollutant source.Keywords: Trembesi leaf; Lead (Pb); Motor vehicle.AbstrakPenelitian ini merupakan penelitian survei yang bertujuan Untuk mengetahui kandungan timbal (Pb) pada daun trembesi (Albizia saman (Jacq.) Merr.) di Taman Kesatuan Bangsa, Jalan Boulevard dan Tugu Boboca, serta melihat hubungan kepadatan lalu lintas dengan kandungan timbal (Pb) pada daun trembesi (Albizia saman (Jacq.) Merr.) di Taman Kesatuan Bangsa, Jalan Boulevard dan Tugu Boboca. Hasil penelitian menunjukkan bahwa Kandungan logam berat timbal (Pb) yang ada di Kota Manado, dibeberapa tempat seperti di Taman Kesatuan Bangsa, Jalan Boulevard dan sekitar Tugu Bobocca berkisar antara 0,59 – 0,84 Ppm. Berdasarkan baku mutu Pb di udara menurut PP No. 41 Tahun 1999 sebesar 2 µg/Nm3 Kandungan Pb di kota Manado masih dibawah ambang batas baku mutu Pb di udara. Namun jika dibandingkan dengan baku mutu lingkungan untuk parameter Pb di udara menurut WHO, dengan batas syarat maksimal yang diperbolehkan adalah sebesar 0,5 µg/Nm3 Kandungan Pb telah melebihi ambang batas cemaran Pb di udara menurut standar WHO. Hubungan kepadatan lalu lintas dengan kandungan timbal (Pb) pada daun trembesi menunjukkan bahwa adanya hubungan antara jumlah kendaraan bermotor dengan kandungan Pb pada daun trembesi , akan tetapi hubungan yang terjadi antara jumlah kendaraan bermotor dengan kandungan Pb ini lemah. Tinggi rendahnya kandungan Pb pada daun tidak hanya di pengaruhi oleh banyaknya jumlah kendaraan yang melintas dijalan, tetapi ada faktor lain yaitu arah dan kecepatan angin, serta jarak pohon dengan sumber pencemar.Kata Kunci : Daun trembesi; Timbal (Pb); Kendaraan bermotor.